Surface-Coated LiNi0.8Co0.1Mn0.1O2 (NCM811) Cathode Materials by Al2O3, ZrO2, and Li2O-2B2O3 Thin-Layers for Improving the Performance of Lithium Ion Batteries - Zhang, Hailin; Xu, Jiaqiang; Zhang, Jiujun (Frontiers in Materials, 2019)
In this paper, the precursor Ni0.8Co0.1Mn0.1(OH)2 is prepared by a co-precipitation method. By mixing this material with LiOH in proportion and sintering twice under 500 and 800°C, respectively, the cathode material of LiNi0.8Co0.1Mn0.1O2 (NCM811) for lithium ion batteries (LIBs) is synthesized. To improve the performance of this NCM811 material, Al2O3, ZrO2, and LBO (Li2O-2B2O3) are, respectively, used to coat it by a wet chemical method. The effects of Al2O3, ZrO2, and LBO thin coating layers (~20–200 nm) on the morphology, structure and electrochemical property of NCM811 are studied using XRD, SEM, TEM, XPS, and electrochemical measurements. Coin LIBs are assembled with the uncoated, Al2O3-coated, ZrO2-coated, and LBO-coated NCM811 cathode materials for performance validation. The experiment results confirm that the charge-discharge specific capacity, Coulomb efficiency, water absorption stability, cycle characteristics, and resistance stability of the NCM811 cathode material can be significantly improved by coating it with LBO particularly. Therefore, the surface coating to the particles of cathode materials using LBO is expected to be an effective and practical modification method to improve the electrochemical performance of LIBs.